How much is memory worth? The case of the “Sexy Sale” - Johnson De la Maza, Tahina Johnson (2020)
The “Sexy Sale” was a recognized torture center with operations during the  dictatorship Augusto Pinochet, mostly between the years 1974 and 1975. The recent news of the real estate sale of the site, declared a national monument in 2016, reveals its imminent danger of disappearing completely. This particular case is intended to be the starting point for a reflection that fundamentally considers the notions of heritage destruction and heritage emotions, discussing some of the public policies associated with the safeguarding of historic sites and places of memory in Chile.